Creative unemployment - Knut Røed; Jens Fredrik Skogstrøm (Institute for the Study of Labor (IZA), 2010)
We examine the impact of job loss on entrepreneurship behavior in Norway. Our identification strategy relies on the use of mass layoffs caused by bankruptcies as indicators of exogenous displacement. We find that working in a company which is going to close down due to bankruptcy during the next four years raises the subsequent entrepreneur rate by 3.7 percentage points (155 %) for men and 1.8 percentage points (180 %) for women, compared to working in a stable firm. These estimates are much larger than what has previously been reported in the literature. Taking into account that many workers lose their jobs in the comparison group of stable firms also, we reckon that the full effects of displacement are even larger.
Keywords: L26; J65; M13; 330; entrepreneurship; self-employment; unemployment